Wireless Inertial Measurement System Provides Accurate Dynamic Angle Change and Angular Data for Body Mount Applications - Harris, Christopher; Mahajan, Sunny; Leslie, Paul; Spani, Carl; Spalteholz, Leo; Hook, William; Livingston, Nigel (CMBES Proceedings, 2010)
No Abstract